Comparative analysis on resistance profiling along tapered semiconductor nanowires: multi-tip technique versus transmission line method. (24th August 2017) - Nägelein, Andreas; Liborius, Lisa; Steidl, Matthias; Blumberg, Christian; Kleinschmidt, Peter; Poloczek, Artur; Hannappel, Thomas
Abstract: The detection of doping dependent values like contact- and path resistances along nanowires (NWs) still proves to be rather challenging compared to planar structures. Unfortunately, the usually used and well established TLM (transmission line measurement) setup exhibits some drawbacks. Complex preliminary preparation steps and the necessity of ohmic contacts limit the investigation to certain semiconductor materials. The simultaneous determination of contact- and path resistances with an unknown distribution makes an analysis on complex structures like tapered nanowires very challenging. Our approach is the utilization of a multi-tip scanning tunneling microscope (MT-STM) as a four point prober, which allows the investigation of freestanding nanowires with an increased spatial resolution. Here, the used measurement setup allows a local separation of current injection and potential measurement and thus a highly precise determination of path resistances. Tapered p-doped GaAs-NWs were used to compare both techniques. Whereas the evaluation of the axial doping profile by MT-STM was rather simple, correction factors had to be introduced for the TLM measurement to calculate the specific resistances and transfer length. By comparing the results of both methods for the very same NW-sample, the precision and accuracy of MT-STM measurements was demonstrated. We found an agreement, which allows the conclusion that both methods exhibit advantages; however the MT-STM was determined as the more precise setup, which enables additional characterization capabilities, such as surface, temperature or light dependent measurements.